HARTA BERSAMA SEBAGAI JAMINAN DALAM AKAD PEMBIAYAAN SYARIAH: ANALISIS YURIDIS TERHADAP PUTUSAN PENGADILAN AGAMA GARUT NO. 3224/PDT.G/2017/PA.GRT - Ahmad Rifat Mathar; Ahmad Zaky Firdaus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This research aims to analyze the legal aspects of using marital joint property (harta bersama) as collateral in Islamic financing contracts in Indonesia through a case study of the Religious Court Decision No. 3224/Pdt.G/2017/PA.Grt in Garut. The method applied is normative juridical with a case study approach, referring to national legislation, judicial precedents, and Islamic legal fatwas. The findings show that although, normatively, explicit consent from both husband and wife is required at the outset of the contract, judicial practice recognizes post-contract ratification as legally valid, provided there is clear evidence of willingness (al-ridha) and no objection from the party holding rights over the joint property. This judicial approach reflects a balance between positive legal principles such as pacta sunt servanda and good faith, and maqāṣid al-syarī‘ah principles emphasizing substantive justice and property rights protection (ḥifẓ al-māl). On the other hand, discrepancies were found between the ideal legal provisions and field practices, where Islamic financial institutions often overlook ownership verification and formal consent regarding collateral used, thereby increasing the potential for future legal disputes.